PARTISIPASI PEMUDA DALAM KONTESTASI POLITIK DI KABUPATEN MAROS (STUDI KASUS : PEMILIHAN CALON ANGGOTA LEGISLATIF TAHUN 2019) - Amul Hikmah (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2020)
This study examines the factors that influence youth participation in legislative elections inMaros regency in 2019. The participation of youth is as participants in the election of a political party.Based on data from the Regional Election Commission (Election Commission) Maros has recorded asmany as 105 young men involved as a legislative candidate Maros regency in 2019. The method usedin this research is qualitative method with descriptive models. The data collection was done byinterview, observation, and focus group discussion (FGD). The informants came from variousbackgrounds political parties and youth organizations. Determination of informants were chosenintentionally (purposive). This study was conducted in Maros, from December 2019 until February2020. The results showed that the factors that influence youth participation in legislative electionscontestation is divided into three: the idealism of youth, power relations and capital, as well as thesupplementary administrative requirements. 1) pertaining to the idealism of youth and youthorganizations during a student activities on campus. 2) The power relations and capital, capitalutilization and the persona of the parents of the young man to come forward to fight. 3) Complementaryadministrative requirements, relating to the regulation of elections that take advantage of youth toparticipate as election participants and carried out by a political party elite as well as the supplementaryadministrative requirements.